Energy Materials - Structure, Properties and Applications - Swain, Bibhu Prasad (Materials Horizons: From Nature to Nanomaterials, 2023)
This book presents the latest progress in energy materials, energy storage, batteries, and supercapacitors. The contents include topics such as fundamentals of energy materials, photovoltaic materials and devices, electrochemical energy conversion and storage, and lighting and light-emitting diodes. Chapters include experimental approaches to device fabrication, photovoltaics and supercapacitors applications, etc. It also discusses energy materials' characterization, preparation methods, and performance testing techniques. The book provides ideas on the design and development of nanoscale devices and covers various applications of nanomaterials. This book is useful for researchers and professionals working in the fields of materials science.